Factor Analysis of Competency Based Trained Graduates of Polytechnic/Technical Universities in Ghana - Mends–Brew, Edwin; Dadzie, Joseph; Dadson, Ben Apau; Amoamah, Martin Owusu (European Scientific Journal, ESJ, 2017)
Higher Education, particularly Polytechnic education which sits at the apex of Technical and Vocational Education and Training (TVET) has undergone a great deal of transformation over the last several years. Polytechnic education was incorporated into the educational system with the primary objective of providing employable skills needed to propel growth in the various sectors of the economy. Therefore, Technical and vocational education and training (TVET) plays a significant role for the socioeconomic development of any country to meet the challenges of skilled labour in the global market and the ever widening digital divide coupled with the development of a knowledge-based economy. Competency Based Training (CBT) which entails the practical aspect of technical and vocational training relates theoretical knowledge to actual practice. For more than a decade, this has been part of the curricula of polytechnic education in Ghana as an alternative method of delivery to equip students with hands-on experience and competencies required in the job market (Salifu et al, 2010). CBT provides an improved form of delivery centered on the integration of acquired knowledge, professional and practical skills and attitude, coupled with a market-driven focus on the student (Afeti et al, 2003). Having churned out graduates through the CBT approach, it is imperative to assess the readiness of these graduates for the job market. It is against this background that the study was conducted to do a ‘Need Analysis’ of these graduates. A total of 55 graduates in two polytechnics were used for the study. The study sought to examine the relative influence of factors influencing career choices of these graduates having been trained through the competency based mode of Teaching and delivery. Factor analysis of ratings of importance of a number of job creation characteristics were used. These results were used to build scales of importance and preference, which were then tested with other variables in a predictive model in which the dependent variable was the decision to be self-employed or to be engaged for employment by third parties upon completion of their respective programmes. The following were found to influence decisions; work-related concerns, gender, age, financial support, family background and internship placements. The results also showed that most of the graduates exhibited that sense of inadequacy towards becoming entrepreneurs or starting their own businesses.